Effectiveness of e-book “Ethno-ecology study of Magnoliopsida in Desa Kiram” to train students’ critical thinking skills - Aufa Nabila; Mochamad Arief Soendjoto; Atiek Winarti (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2023)
Students use their smartphones for daily tasks whenever and wherever they go, and they interact with their surroundings more directly as a result. One media that carries out the advancement of technology and communication is electronic books or e-books. E-books are one kind of educational resource that needs to be created because students may easily access them only using smartphones, either offline or online. Local learning resources can be used to train critical thinking skills. This development research aims to examine the expectation and actual effectiveness of e-books to train students’ critical thinking skills. The research method used Tessmer’s formative evaluation design. The research results show that expected effectiveness got an N-gain score of 0.47 in the medium category, and actual effectiveness got an N-gain score of 0.50 in the medium category. In conclusion, it shows that the e-book “Ethno-Ecology Study of Magnoliopsida in Desa Kiram” is to be used as training material for students’ critical thinking skills.Abstrak Penggunaan smartphone tidak terlepas dari kegiatan sehari-hari kapanpun dan di manapun mahasiswa berada, serta mahasiswa lebih sering berinteraksi langsung dengan lingkungan sekitar mereka. Salah satu media yang mengimplementasikan perkembangan teknologi dan komunikasi adalah E-book. E-book menjadi media pembelajaran yang perlu dikembangkan karena mudah diakses oleh mahasiswa hanya dengan penggunaan smartphone secara offline ataupun online. Sumber belajar berpotensi lokal dapat digunakan dalam melatihkan keterampilan berpikir kritis. Penelitian pengembangan ini bertujuan untuk menguji keefektifan harapan dan aktual e-book dalam melatihkan keterampilan berpikir kritis mahasiswa. Metode penelitian menggunakan desain evaluasi formatif Tessmer. Hasil penelitian menunjukkan keefektifan harapan memperoleh skor N-gain 0,47 dengan kategori sedang, dan keefektifan aktual memperoleh skor N-gain 0,50 dengan kategori sedang. Kesimpulan hasil penelitian menunjukkan bahwa e-book “Kajian Etno-Ekologi Magnoliopsida di Desa Kiram” yang dikembangkan efektif dalam melatih keterampilan berpikir kritis mahasiswa.